2017
DOI: 10.14814/phy2.13267
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term heat stress alters redox balance in porcine skeletal muscle

Abstract: Heat stress contributes to higher morbidity and mortality in humans and animals and is an agricultural economic challenge because it reduces livestock productivity. Redox balance and associated mitochondrial responses appear to play a central role in heat stress‐induced skeletal muscle pathology. We have previously reported increased oxidative stress and mitochondrial content in oxidative muscle following 12 h of heat stress. The purposes of this investigation were to characterize heat stress‐induced oxidative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 32 publications
4
17
0
Order By: Relevance
“…While it is likely that endotoxemia contributed to inflammatory signaling in these muscles the possibility of other mediators cannot be eliminated. For example, we also found increased oxidative stress in these tissues (Volodina et al 2017) and oxidative stress has been previously shown to lead to inflammatory signaling (Pizza et al 1998). In addition, in skeletal muscle heat stress failed to increase expression of heat shock proteins, however in intestinal samples from these animals they were elevated .…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…While it is likely that endotoxemia contributed to inflammatory signaling in these muscles the possibility of other mediators cannot be eliminated. For example, we also found increased oxidative stress in these tissues (Volodina et al 2017) and oxidative stress has been previously shown to lead to inflammatory signaling (Pizza et al 1998). In addition, in skeletal muscle heat stress failed to increase expression of heat shock proteins, however in intestinal samples from these animals they were elevated .…”
Section: Discussionsupporting
confidence: 63%
“…For example, we also found increased oxidative stress in these tissues (Volodina et al. 2017) and oxidative stress has been previously shown to lead to inflammatory signaling (Pizza et al. 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When the ambient temperature exceeds the thermoneutral zone (16 to 22 • C for growing-finishing pigs), the pigs are considered to be heat-stressed [4]. Chronic hyperthermia leads to increased oxidative stress in various cells and tissues including skeletal muscle [5,6]. The oxidative reaction induced by heat stress has a considerable influence on meat quality.…”
Section: Introductionmentioning
confidence: 99%